Pengaruh Core Stability Exercise Secara Kelompok Dan Individu Terhadap Low Back Pain Myogenik Pada Pembuat Batu Bata Di Desa Maron - Chintia Alkuratu, Lucky, Dwi Kurniawati, SSt.FT, Yulisna Mutia Sari, SSt.FT., M.Sc () (2015)
Background : Low back pain myogenik is an unpleasant sensory and emotional experience in toracal vertebrae to under hip which is caused by petentional defective or tissue defective (Paliyama, 2003). Some jobs which can cause this illness is sitting in a long time and defending postur. Working in a certain sitting position for along time is done by brick makers physiotherapy treatment can be given them is core stability exercise grouply and individually. Aim : This research aims to know influential of core stability exercise grouply and individually toward low back pain myogenik on brick makers in Maron village. Research method : This research is held through quantitative approach with Quasi Experimental Design pre and post with control group design method. Research population is brick makers in Maron village, sample amount is 40 people with exercising grouply and individually. Result : Result test value of wilcoxon test get the value < 0,05 when the experiment has significant pain value 0,000 it means there are pre and post pain influential toward pain decrease. Conclusion : There are influential of core stability exercise groply and individually toward low back pain myogenik on brick makers in Maron village.